De Franciscus Xaveriusvereniging in Sittard en omstreken (1868-1900) - Jacobs, Antoine (Studies over de sociaaleconomische geschiedenis van Limburg, 2022)
From the mid-nineteenth century Catholic elites increasingly engaged in charity to combat pauperization, secularization, and moral decay. In 1854, in Brussels, the Jesuit Louis Van Caloen founded the Franciscus Xavier Society, a brotherhood that aimed to harmonize social relations and would become very large in Belgium. According to Van Caloen conversion and prayer were imperative to improve the conditions of workers, but the Society also invested in social relief. Although his attempts to spread the rather paternalistic FXS in the Netherlands largely failed, the brotherhood was remarkably successful in Sittard and several neighbouring villages, where hardly any industrial workers lived. The Sittard branch of the FXS was founded in 1868. Under the leadership of the Jesuit Antonius van der Leeuw, the association got off to a flying start and undertook various religious and social activities, including the establishment of a savings bank. From 1895, however, membership sharply declined and in 1900 the Sittard FXS was disbanded.